2020
DOI: 10.2459/jcm.0000000000001129
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and hospital course of patients admitted for acute cardiovascular diseases during the coronavirus disease-19 outbreak

Abstract: Introduction During the coronavirus disease-19 (COVID-19) outbreak in spring 2020, people may have been reluctant to seek medical care fearing infection. We aimed to assess the number, characteristics and in-hospital course of patients admitted for acute cardiovascular diseases during the COVID-19 outbreak. Methods We enrolled all consecutive patients admitted urgently for acute myocardial infarction, heart failure or arrhythmias from 1 March to 31 May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 12 publications
0
31
1
Order By: Relevance
“…Of these, the majority were from Europe with one from Australia 17 and two from Asia. 18 , 19 One reported overall CV disease, which included heart failure (HF), acute myocardial infarction, and arrhythmias, 20 eight described acute coronary syndromes (ACS), and six described HF. Most studies used the same period in a preceding year for comparison, to account for seasonal variability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the majority were from Europe with one from Australia 17 and two from Asia. 18 , 19 One reported overall CV disease, which included heart failure (HF), acute myocardial infarction, and arrhythmias, 20 eight described acute coronary syndromes (ACS), and six described HF. Most studies used the same period in a preceding year for comparison, to account for seasonal variability.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies reported a decline in admission rate during the COVID-19 pandemic, ranging from a 1% 23 to 81% 19 reduction, with only four reporting an increase in admission rate. 18 , 20 , 22 , 24 The mean age of patients was 68 years in both COVID-19 and comparator cohorts and the percentage of male patients was 68% and 67%, respectively. The median length of the COVID-19 observation period was 55 [IQR 30–54] days compared with 60 [IQR 30–120] days in the comparator period.…”
Section: Resultsmentioning
confidence: 99%
“…Almost half of PWE presented reluctance to seek medical care and 61.4% felt unsafe about going to the hospital. Delayed arrival at the emergency department due to reluctance to seek medical care has been reported in several studies [23][24][25][26]. Therefore, it should be emphasized to PWE that measures are in place to assure safety in the hospital and that non-COVID-19-related healthcare should not be postponed.…”
Section: Discussionmentioning
confidence: 99%
“…a dual track system) are able to face the adverse effects of the pandemic in terms of in-hospital mortality containment for AMI and stroke patients, ensuring appropriate levels of clinical care for admitted patients with non-Covid and non-deferrable clinical conditions. Moreover, as suggested by recent studies [38], better communication strategies should be implemented in epidemic times by public health authorities to ensure timely presentation of individuals (preventing the huge increase in time to door registered during Covid-19 outbreak) with acute non-deferrable diseases such as AMI and stroke. This is particularly important in a regional context where the strong impact caused by Covid epidemic has moved experts and health managers on re-thinking the system supporting the best practices which have been able to timely and safely help in reacting to the unexpected health emergency ( [39,40]).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the relevant increase in time from the onset of symptoms to hospital presentation, indeed data on other outcomes also need to be considered (e.g. in-hospital heart failure, need for inotropic infusion, ejection fraction at discharge) in future studies to investigate more in depth if any relevant adverse effect (in addition to mortality rate) has been experienced by AMI and stroke patients during Covid-19 time [37,38].…”
Section: Plos Onementioning
confidence: 99%